2019
DOI: 10.1371/journal.pone.0212557
|View full text |Cite
|
Sign up to set email alerts
|

Psychological factors and premenstrual syndrome: A Spanish case-control study

Abstract: Objective To assess whether the psychological variables perceived stress, neuroticism and coping strategies, are associated with Premenstrual Syndrome (PMS) and Premenstrual Dysphoric Syndrome (PMDD). Design Case-control study with incident cases using the Spanish public healthcare system. Setting 3 major public hospitals and one family counseling and planning center. Population Women consulting for troubles relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 27 publications
3
35
1
4
Order By: Relevance
“…Premenstrual symptoms like anger and irritability may be associated with stress-related premenstrual decline in brain serotonin function, resulting in the worsening of cardinal mood symptoms. 50 This was in agreement with other studies conducted in Spain, 51 Iowa in the USA 52 53 and India. 54 …”
Section: Discussionsupporting
confidence: 91%
“…Premenstrual symptoms like anger and irritability may be associated with stress-related premenstrual decline in brain serotonin function, resulting in the worsening of cardinal mood symptoms. 50 This was in agreement with other studies conducted in Spain, 51 Iowa in the USA 52 53 and India. 54 …”
Section: Discussionsupporting
confidence: 91%
“…The present study demonstrates that negative subjective perception of health is significantly related to premenstrual symptomatic features, including its prevalence, type, and severity, in college students. As substantial evidence from earlier PMS research has shown [2, 1519], this study also clarified that self-rating stress strongly relates to premenstrual symptomatology as assessed by MDQ scores. We further revealed that the 19 women who evaluated themselves as “unhealthy and stressed” had greater prevalence of severe or extremely severe premenstrual complaints consisting of general aches and pains, confusion, lowered school or work performance, decreased efficiency, loneliness, anxiety, restlessness, mood swings, and depression.…”
Section: Discussionsupporting
confidence: 75%
“…We performed multiple linear regression analysis with stepwise selection to determine how well the combination of the seven independent variables (age, BMI, subjective perception of health, self-rating stress, regular exercise habits, breakfast eating habits, and sleep duration) explains the variance in the MDQ total scores. We should mention that, referring to previous studies [2, 5, 1525], these seven variables were selected as potential factors that may be related to the premenstrual-symptom constellation. As Table 4 shows, multivariable analysis revealed subjective perception of health (β = 0.28; p < 0.001) and self-rating stress (β = 0.18; p = 0.008) as the factors most strongly related to the severity of premenstrual symptoms evaluated by the MDQ total scores.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] Perceived stress, neuroticism, and coping strategies have been reported to be strongly related to PMDs. 10 Perceived injustice is a belief linked to unfair treatment and unnecessary suffering caused by illness. 11 Perceived injustice has been extensively analyzed among people with chronic pain, including those with whiplash, fibromyalgia, and osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%